Resistance to Single-agent Chemotherapy for Low-risk Gestational Trophoblastic Neoplasia - Shahrzad Sheikhhasani; Aghdas Abdolrazaghnejad; Azam sadat Mousavi; Setareh Akhavan; Narges Zamani; Elham Feizabad (Babol University of Medical Sciences, 2023)
Background: Methotrexate (MTX) and actinomycin D (ActD) have been used as first-line chemotherapy agents in the treatment of low-risk gestational trophoblastic neoplasia (GTN). Although low-risk GTN is considered a curable disease, its reported primary remission rates of 49 to 93% reflect the difficulties of treatment and different factors influencing it. Hence, this study aimed to determine the remission rates and related factors of single-agent chemotherapy resistance in low-risk GTN patients. Methods: This retrospective study included patients with diagnosed low-risk GTN who received either MTX once a week (IM, 30mg/m2) or ActD once every two weeks (pulsed IV, 1.25mg/m2). Then, the patients were followed-up until complete remission or single-agent treatment failure to assess resistance rate and related factors.   Results: Eighty-four patients were included in the study (18 patients were receiving MTX and 66 patients were receiving ActD). 85.7% of all participants achieved complete remission after first-line chemotherapy (72.2% in MTX vs 89.4% in ActD). There was a significant association for higher tumor size (P=0.046), the occurrence of metastasis (P=0.019), and pretreatment β-HCG levels (P=0.005) with resistance to treatment. Conclusion: This study demonstrated higher tumor size, the occurrence of metastasis, and pretreatment β-HCG levels have been associated with increased resistance to first-line chemotherapy agents.